Days of wonder : a novel - Leavitt, Caroline (Algonquin Books of Chapel Hill, 2024)
"As a teenager, for a moment, Ella Fitchburg found love--yearning, breathless love--that consumed both her and her boyfriend, Jude, as they wandered the streets of New York City together. But her life was unexpectedly upended when she was accused of trying to murder Jude's father, an imperious superior court judge, and sentenced to twenty-five years in prison. When she learns she's pregnant shortly after sentencing, she reluctantly decides to give up the child. Ella is released after serving only six years. While she is desperate to turn the page on a new life, she can't seem to let go of her past. With only an address as a possible lead, she moves to Ann Arbor, Michigan, determined to get her daughter back. Forced to hide her identity and complicated past and live in a constant state of deception, she finds that what she's been searching for all along is a way to uncover and live with the truth. Yet a central mystery neither Jude nor Ella can remember the events leading up to the attempted murder--that fateful night which led to Ella's conviction."--